Transmission of global financial shocks to EMU member states: The role of monetary policy and national factors - Maria Gelman; Axel Jochem; Stefan Reitz (Deutsche Bundesbank, 2016)
The paper analyses the transmission of global financial shocks to individual member states of the European Monetary Union (EMU), in which monetary policy is delegated to the ECB and financial markets are fully integrated. Using a panel VAR model, we show that the asymmetric effects of global shocks on member states are partly offset by the uniform access of commercial banks to the Eurosystem's open market operations in conjunction with the redistribution of liquidity via the TARGET mechanism. However, an appropriate policy mix of sound public finances, solid financial regulation and targeted macroprudential measures is necessary in order to safeguard macroeconomic sustainability without needing to manage capital flows.
Keywords: F32; F36; F45; 330; monetary union; capital flows; global financial cycle; macroeconomic imbalances